1995
DOI: 10.5860/crl_56_01_33
|View full text |Cite
|
Sign up to set email alerts
|

Customer Expectations: Concepts and Reality for Academic Library Services

Abstract: ver the past two decades technological innovations have provided libraries with the means to not only meet but also surpass customer needs and expectations. Initially, technology involved the automation of library staff functions, and customers experienced few benefits directly. With the development of the online catalog, customers experienced a faster, easier, and more efficient method of searching. As online systems became commonplace, librarians began to realize the new and exciting possibilities to which i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
2

Year Published

1996
1996
2014
2014

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 3 publications
0
16
0
2
Order By: Relevance
“…Additionally, libraries are not always run by people who actually like their jobs, and thus may not be willing to help the users. A number of research studies (see Shi et al, 2004;Martensen & Gronholdt, 2003;Cullen, 2001;Flanagan & Horowitz, 2000;Hernon, Nitecki & Altman, 1999;Heckart, 1999;Millson-Martula & Menon, 1995;Green, 1990), therefore, emphasized that the libraries need to focus on users' needs, their expectations and satisfaction in order to resolve these problems.…”
Section: User Satisfaction and Dissatisfactionmentioning
confidence: 98%
See 1 more Smart Citation
“…Additionally, libraries are not always run by people who actually like their jobs, and thus may not be willing to help the users. A number of research studies (see Shi et al, 2004;Martensen & Gronholdt, 2003;Cullen, 2001;Flanagan & Horowitz, 2000;Hernon, Nitecki & Altman, 1999;Heckart, 1999;Millson-Martula & Menon, 1995;Green, 1990), therefore, emphasized that the libraries need to focus on users' needs, their expectations and satisfaction in order to resolve these problems.…”
Section: User Satisfaction and Dissatisfactionmentioning
confidence: 98%
“…Millson-Martula and Menon (1995) recommended considering users as customers and as individuals, and noted that gaps exist between the library and its customers. According to them, lack of interaction between the library and the users is one of the major gaps.…”
Section: Causes Of Dissatisfactionmentioning
confidence: 98%
“…Viewing users as customers was first mentioned by Millson-Martula and Menon (1995). They report that gaps between the library and customers exist, such as the lack of interaction between library staff and the students and faculty.…”
Section: Library Usementioning
confidence: 99%
“…In the 1980s, library users were regarded as end-users, and Ojala was the first to propose in 1986 that libraries treat users as customers and must be able to meet their demands should. Considering the importance of users to libraries, researchers have proposed that library management consider user needs as well as customer expectation and satisfaction in setting management goals (Green, 1990;Millson-Martula and Menon, 1995;Heckart, 1999;Hernon et al, 1999;Flanagan and Horowitz, 2000;Cullen, 2001;Martensen and Gronholdt, 2003;Shi et al, 2004). Since the emergence of a network environment, libraries have to pay close attention to their customers' opinions (Cullen, 2001;Van Groenendaal, 1997;Xie, 2006;Koohang and Ondracek, 2005).…”
Section: Library Service Developmentmentioning
confidence: 99%
“…Numerous studies have demonstrated that the importance of library service is users-oriented and the needs of meeting their demand and expectation [1][2][3][4][5][6][7][8]. The proliferation of information technology (IT) brings users" needs for timelier, convenient, speedy information delivery in recent years.…”
Section: Introductionmentioning
confidence: 99%